Examining students’ intention to perform voluntary blood donation using a theory of planned behaviour: A structural equation modelling approach - M. Tanveer Hossain Parash; Norazah Mohd Suki; S. C. Shimmi; A. B.M.Tofazzal Hossain; Krishna Dilip Murthy (2020)
Objective This study aims to examine the behavioural intention of students to make voluntary blood donations. Moreover, it uses a theory of planned behaviour as its guiding principle and does so within the context of Malaysia, a developing nation. Methods Data were collected via a self-administered questionnaire from a sample of 500 students at a public higher learning institution in Malaysia. Structural equation modelling approach (SEM) was performed to assess the strength of the hypothesized relationships of the proposed model simultaneously via the two-stage model-building process. Results The SEM approach revealed that knowledge was the most influential predictor of students’ intention to make a voluntary blood donation. With the knowledge that the more blood they donate, the more lives will be saved, the inclination to donate blood is intensifying among students. Moreover, all of the TPB constructs applied were also seen to significantly influence students’ response to voluntary blood donation. Conclusions The nexus of attitude, subjective norm, perceived behavioural control, and knowledge about students’ intention to perform voluntary blood donation are evidenced in a developing nation. The implications of the study and directions for future research are provided.